2017
DOI: 10.1084/jem.20150237
|View full text |Cite
|
Sign up to set email alerts
|

NLR members NLRC4 and NLRP3 mediate sterile inflammasome activation in microglia and astrocytes

Abstract: Lysophosphatidylcholine is associated with neurodegeneration and demyelination. Freeman et al. demonstrate that lysophosphatidylcholine triggers NLRP3- and NLRC4-dependent inflammasome activation, and in a synergistic fashion, NLRP3 and NLRC4 contribute to a cuprizone-induced demyelination model in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
263
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(285 citation statements)
references
References 96 publications
18
263
2
2
Order By: Relevance
“…However, microglia are also critical for an extensive and often sustainable (up to years) generation of cytokines (for example, IL-1β and IL-6) and ROS, which in turn recruit neutrophils and blood monocytes-macrophages to the injured area 103,105,108 . Furthermore, complement 109 or lysophosphatidylcholine activates inflammasomes in microglia or astrocytes soon after TBI and during neuro-inflammation 110 . After exposure to IL-1β, astrocytes rapidly generate immune signals in the form of extracellular vesicles dispatched to the periphery, which results in the further recruitment of neutrophils and systemic release of cytokines 111 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…However, microglia are also critical for an extensive and often sustainable (up to years) generation of cytokines (for example, IL-1β and IL-6) and ROS, which in turn recruit neutrophils and blood monocytes-macrophages to the injured area 103,105,108 . Furthermore, complement 109 or lysophosphatidylcholine activates inflammasomes in microglia or astrocytes soon after TBI and during neuro-inflammation 110 . After exposure to IL-1β, astrocytes rapidly generate immune signals in the form of extracellular vesicles dispatched to the periphery, which results in the further recruitment of neutrophils and systemic release of cytokines 111 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…Therefore, insights into the regulation of NLRP3 in macrophages may not necessarily reflect the same regulatory dynamics of NLRP3 in microglia, especially in regards to their tendencies for pyroptosis or non-pyroptotic inflammation. One study found that murine microglia primed with LPS and then stimulated with the DAMP lysophosphatidylcholine led to NLRP3 mediated inflammation; however, cytotoxicity of microglia was not dependent on NLRP3 canonical or non-canonical activation (Freeman et al, 2017). An additional study using murine microglia also found that a two-step activation paradigm regulates NLRP3 inflammasome activation in response to TLR4 stimulation (Sanz and Di Virgilio, 2000).…”
Section: Priming and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…The list of NLRP3 activators is extensive and includes Gram‐positive and ‐negative bacteria, bacterial toxins, DNA and RNA viruses, fungi, and protozoa . In addition, NLRP3 can sense a variety of DAMPs, including ATP, uric acid crystals, silica crystals, saturated fatty acids, asbestos, extracellular histones, lysophosphatidylcholine, aluminum hydroxide, and bee venom . It is currently hypothesized that rather than direct binding of NLRP3 to the ligand, the repertoire of diverse ligands triggers a common set of cellular events that culminate in the activation of NLRP3.…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
“…For instance, mouse macrophages exposed to hyperosmotic stress produce IL‐1β in a manner dependent on both NLRC4 and NLRP3 inflammasome activity . Likewise, NLRC4 and NLRP3 mediate sterile inflammasome activation in microglia and astrocytes in response to the DAMP lysophosphatidylcholine . Finally, in a rodent model of stroke, the NLRC4 and AIM2 inflammasomes contribute to ischemic brain injury in a manner that required ASC but not NLRP3 …”
Section: Naip‐nlrc4 Inflammasomementioning
confidence: 99%